Blowup of Solutions to the Compressible Euler-Poisson and Ideal MHD Systems - Wenming Hu (Advances in Mathematical Physics)
In the present paper, we study the blowup of the solutions to the full compressible Euler system and pressureless Euler-Poisson system with time-dependent damping. By some delicate analysis, some Riccati-type equations are achieved, and then, the finite time blowup results can be derived.